On the Lauwerier formulation of the temperature field problem in oil strata - Lyubomir Boyadjiev; Ognian Kamenov; Shyam Kalla (International Journal of Mathematics and Mathematical Sciences)
The paper is concerned with the fractional extension of the Lauwerier formulation of the problem related to the temperature field description in a porous medium (sandstone) saturated with oil (strata). The boundary value problem for the fractional heat equation is solved by means of the Caputo differintegration operator D∗(α) of order 0<α≤1 and the Laplace transform. The solution is obtained in an integral form, where the integrand is expressed in terms of a convolution of two special functions of Wright type.